TAX CENTER UKI DENGAN KANWIL DJP JAKARTA TIMUR MENDAMPING WARGA LAPOR PAJAK - Milko Hutabarat; Agustina Indriani; Parlin Bachtiar Sinaga (Jurnal Abdimas Bina Bangsa, 2024)
This Community Service (PKM) activity was carried out, thanks to the cooperation agreement between the Tax Center of  the Indonesian Christian University (UKI) and the Directorate General of Taxes of the East Jakarta Regional Office (Kanwil). Filling and reporting personal income tax e-SPT activities are intended for all lecturers, UKI employees to community members. The series of activities are also accompanied by guidance on matching (validating) the Taxpayer Identification Number (NPWP) with the National Identity Number (NIK). The method used is to provide assistance to Individual Taxpayers who directly come to the UKI Campus accompanied by the Head of the UKI Tax Center, namely the Head of the UKI Tax Center Technical Implementation Unit   , Milko Hutabarat, S.E., S.H., M.Si. and also parties from the DGT East Jakarta Regional Office. Although this activity lasted only 1 day, the results of this activity have attracted enthusiasm from at least 75 Wajb Pajak.  This event is very helpful for taxpayers who find it difficult to match NPWP and NIK and also report Tax Returns (income). On the other hand, this also aims to be a real learning tool, for UKI students, where they are directly involved in the socialization process and assistance in filling and reporting tax returns with  an online (electronic) system